Experimental Study on Strength and Permeability Characteristics of Cemented Rock-Tailings Backfill - Qiu, Huafu; Zhang, Fushun; Sun, Weibo; Liu, Lang; Zhao, Yujiao; Huan, Chao (Frontiers in Earth Science, 2022)
To study the strength and permeability characteristics of cemented tailings backfill with different cement-sand ratios and different waste rock contents, uniaxial compression strength test, and permeability test were carried out respectively. The porosity of cemented tailings backfills after solidification was observed by scanning electron microscope. The effects of cement-sand ratio and waste rock content on the internal porosity and overall permeability of cemented tailings backfill were studied. The test results show that the cement-sand ratio and waste rock content have certain effects on the strength and permeability of the backfill body. When the cement-sand ratio was fixed, the uniaxial compressive strength and permeability of the backfill body increased firstly and then decreased with the increase of waste rock content. When the waste rock content was 10 %, the uniaxial compressive strength of the backfill body reached the maximum, and when the waste rock content was 30 %, the permeability reached the maximum. Due to the increase of the area of waste rock particles in the cross-section, the area of gas passing rapidly decreased, resulting in the decrease of the permeability growth rate. When the waste stone content was fixed, with the decrease of cement-sand ratio, due to the decrease of cementitious materials, more micro-cracks were produced in the curing process of backfill body, resulting in the decrease of uniaxial compressive strength and the increase of permeability.